Optimization Of Legal Awareness, Population Administration, And Basic Education Through Community Service In Dembek Village, Momi Hall - Enny Martha Sasea; Natalia Rahmadani Papuana Dewi; Hengki Saiba (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The implementation of the Tri Dharma of Higher Education through community service programs is a strategic instrument to bridge the gap between academic theory and empirical reality. This article examines the implementation of the Community Service (PKM) program by a team of lecturers from the Manokwari College of Law (STIH) in Dembek Village. in Dembek Village, Momi Waren District, South Manokwari Regency. Using the Participatory Action Research method, the intervention focused on increasing legal awareness for the protection of vulnerable groups, structuring population administration, internalizing national insight, eradicating illiteracy through basic literacy guidance, and revitalizing higher education infrastructure. The results of the field research indicate that the cultural and participatory approach has proven effective in breaking down the sociological barriers of the community. There is a significant increase in public understanding of basic legal rights, administrative procedures for civil registration, improvement of academic facilities, and acceleration of the cognitive capabilities of elementary school-aged children. The synthesis of these findings confirms that the integration of local wisdom and public policy socialization is an absolute prerequisite in creating social resilience and inclusive village governance in rural areas.